Endocrine system 3: thyroid and parathyroid glands - John Knight (Endocrine system 3: thyroid and parathyroid glands, 2021)
The endocrine system comprises glands and tissues that produce hormones for regulating and coordinating vital bodily functions. This article, the third in an eight-part series, looks at the thyroid and parathyroid glands.